Thoracotomy of an asymptomatic, functional, posterior mediastinal paraganglioma: A case report - Yin, Yi-Yu (World J Clin Cases, 2019)
BACKGROUND: Paragangliomas in the mediastinum are rare, accounting for only 1%-2% of all paragangliomas and < 0.3% of all mediastinal tumors. Most paragangliomas are nonfunctional, therefore, asymptomatic functional paragangliomas in the left posterior mediastinum are extremely rare. Perioperative management including preoperative preparation, careful intraoperative procedures, and strict postoperative care is important, and one-stage surgical resection should be performed only after appropriate perioperative measures are undertaken. Because those tumors are rare, it is necessary to report known cases to raise awareness regarding them. CASE SUMMARY: We report the case of a 47-year-old male who was admitted to our hospital with the chief complaints of intermittent tearing pain on the left side of the chest and back for more than 10 mo. A chest contrast-enhanced computed tomography scan revealed a round, solid mass in the left posterior mediastinum, with low-density cystic lesions in the middle, and no enlarged lymph nodes in the hilum or mediastinum (Figure 1). After the diagnosis of paraganglioma, the patient was preoperatively given an oral adrenoceptor blocking drug (phenoxybenzamine), and intravenous fluid resuscitation for two weeks, subsequently the patient underwent a one-stage resection of lesions via left thoracotomy. The patient’s blood pressure increased to 220/120 mmHg when the tumor was touched, which could be relieved by symptomatic treatment such as accelerating liquid transfusion or other intervention to lower blood pressure. The patient recovered uneventfully after surgery, with no abnormal blood pressure or recurrence during one year of follow-up visits. CONCLUSION: Surgical resection is the preferred treatment for asymptomatic functional paragangliomas.